THE IMPLEMENTATION OF PREDICTION STRATEGY IN IMPROVING STUDENTS’ READING COMPREHENSION ON ENGLISH RECOUNT TEXT - Nurfhany Hasruddin; Syamsiarna Nappu; Eka Prabawati Rum (FKIP Unismuh Makassar, 2021)
The aim of this research was to identify the implementation of a prediction strategy to improve students' reading comprehension of English recount text and student responses in reading through a prediction strategy. The researcher used pre-experimental research and carried out pre-test, treatment and post-test designs and collected test-based data. The sample was a class VIII.D student at MTs. Negeri Luwu Timur, a total of 28 students in the academic year 2020/2021. This sample was taken randomly by lottery. Variables are dependent and independent variables. The data was analyzed using SPSS. The showed that class VIII.D student pre-test results were of sufficient value. The results of this study were that the mean value obtained by the students through the pre-test was (58,14) while the post-test was observed (82,29) as result, the significant value of the paired sample test is lower than the significant level, i.e. 0.000 <0.05. Then find the value of the table t of 1,673. This is because the t value is 40,616>1,673. From these data, it is shown that the use of the prediction strategy in improving students’ reading comprehension on recount text, it can be concluded from the above data that the student's reading comprehension has been improved by using the prediction strategy as a learning tool and students’ can be active in the learning process through the use of the prediction strategy.